Identification of Religious and Morals Values of Early Childhood in Literacy Bag Activities at RA Wadas Kelir Purwokerto - Khomsiyatun, Umi; Hidayat, Imam; Hamid Samiaji, Mukhamad; Marlina (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
The cultivation of religious and moral values in early childhood is important to do. Because recently there have been many cases of sexualharassment and other uncharacteristic behavior. Early childhood education institutions are a strategic place to instill religious and moralvalues from an early age. RA Wadas Kelir as one of the ECCE institutions in Banyumas is able to instill religious and moral values well.Through the Literacy Bag program, it is able to produce the output of students who are literate and have character. The purpose of this studywas to identify religious and moral values of early childhood resulting from the literacy bag program at RA Wadas Kelir Purwokerto. Thisresearch is included in qualitative descriptive research with a case study method. The research was conducted at RA Wadas Kelir Purwokertowhich is located on Jl. Wadas Kelir RT. 07 RW. 05 Karangklesem, South Purwokerto, Banyumas Regency. The informants in this study were31 students, who were found in two classes, namely Ibu Sina's class (17 children) and Ibn Zahrawi's class (14 children). Data collectiontechniques are carried out by interviews, observations, and documentation. The results showed that in the implementation of the Literacy Bagactivities in RA Wadas Kelir, religious and moral values were found in children which were shown by knowing god through his religion,imitating worship movements Accustomed to behaving well, polite, polite, honest, responsible , helpful, sportive, and respecting the religioustolerance of others.